Internal customer satisfaction toward service quality: A case study in Human Resource Department Tenaga Nasional Berhad Malacca / Muhamad Afiq Azmi and Khairulnazrin Abdullah - Azmi, Muhamad Afiq; Abdullah, Khairulnazrin (Faculty of Administrative Science and Policy Studies, 2013)
Both public and private sectors have given much attention to the concept of customer satisfaction in the past couple of decades. While most companies have developed strategies to improved quality and external customer service, internal customer satisfaction is a much neglected component of quality improvement. Keeping internal customers satisfied and happy is the first step towards creating external customer satisfied with the product or services given. This study purposes to help Human Resource Department of TNB Malacca to know what are others departments perceptions toward their service quality. The total number of employees from 97 respondents been selected from seven departments and been given questionnaire to answer the questions based on three main aspects of serve quality which are communication, reliability and responsiveness. Data collected been analyzed by SPSS software and not surprisingly the findings bring good news to Human Resource Department of TNB Malacca. Most of the respondent generally satisfied with the service quality at Human Resource Department. Hence, this study give evidence that Human Resource Department at TNB Malacca is already good in service their internal customer.